Are Economists' Preferences Psychologists' Personality Traits? A Structural Approach - Tomáš Jagelka (Institute of Labor Economics (IZA), 2020)
This paper proposes a method for empirically mapping psychological personality traits to economic preferences. Careful modelling of random components of decision making is crucial to establishing the long supposed but empirically elusive link between economic and psychological systems for understanding differences in individuals' behavior. I use factor analysis to extract information on individuals' cognitive ability and personality and embed it within a Random Preference Model to estimate distributions of risk and time preferences, of their individual-level stability, and of people's propensity to make mistakes. I explain up to 50% of the variation in both average risk and time preferences and in individuals' capacity to make consistent rational choices using four factors related to cognitive ability and three of the Big Five personality traits. True differences in desired outcomes are related to differences in personality whereas actual mistakes in decisions are related to cognitive skill.
Keywords: D91; D80; D01; 330; economic preferences; personality traits; decision error; measurement error; stochastic discrete choice